A combination of carfilzomib, dexamethasone, and daratumumab for treatment of adult patients with relapsed/refractory multiple myeloma in two dosing regimens: once-weekly and twice-weekly. Issue 12 (2nd December 2021) - Leleu, Xavier; Chari, Ajai; Richard, Shambavi; Khurana, Monica; Yusuf, Akeem; Usmani, Saad Z.
ABSTRACT: Introduction: Despite the development of new therapeutic agents, relapsed/refractory multiple myeloma (RRMM) is associated with poor survival outcomes. Furthermore, many patients develop resistance to immunomodulatory drugs (IMiD), creating a need for IMiD-free regimens. Areas covered: This review focuses on the combination of carfilzomib, dexamethasone, and daratumumab (KdD or DKd) which has shown promising results in patients with RRMM who have tried multiple lines of therapy, and has been approved in the U.S., EU, and Japan. The KdD triplet has two recommended dosage regimens, carfilzomib once-weekly (KdD70 QW) and carfilzomib twice-weekly (KdD56 BIW), with comparable efficacy and safety profiles. Expert opinion: These options provide flexibility to patients and healthcare providers, especially in the era of COVID-19. Carfilzomib-based regimens remain a standard of care based on multiple randomized phase 3 studies. Additional studies are currently underway investigating carfilzomib-based regimens such as KdD combined with novel agents. Nevertheless, KdD is one of the most efficacious options for patients with RRMM.